Investigation of thermal effect on solidification in Sn/Cu interconnects during self-propagating exothermic reaction bonding. (November 2022) - Liang, Shuibao; Zhong, Yi; Robertson, Stuart; Liu, Allan; Jiang, Han; Liu, Canyu; Zhou, Zhaoxia; Liu, Changqing
Abstract: Self-propagating exothermic reaction (SPER) of alternating metal nanolayers provides intense localised heat that allows bonding of metals or alloys under ambient temperature. However, the formation of the bonds through the rapid heating and cooling confined at the bonding interfaces is a non-equilibrium process, and the thermal effect on solidification and manufacturing reliability is yet to be understood. In this work, the Cu/Sn-nanofoil-Sn/Cu interconnects (where Sn is a solder layer) prepared via SPER of Ni/Al nanofoil are studied by numerical simulations and experiments to understand the thermal transfer and its effect on the solidification. It has been found that the SPER completes within a few milliseconds, the temperature at solder/Cu interface can be higher than the melting point of solder, and the cooling rate can be as high as 1.5 × 10 7  °C/s, the maximum temperature gradient can reach 5.40 × 10 7  °C/m. The microstructure predicted by simulation agrees well to the experimental results: the columnar dendrites are formed in the solder during the cooling stage, and the columnar structures prefer to form and grow in the solder region due to the high cooling rate. Highlights: Combined macro thermal transfer simulation with phase field modelling Predicted thermal affects during self-propagating exothermic reaction bonding Simulated solidification of solder under rapid cooling rate Simulated temperature and columnar grains agree well with the experiment.